Review of observations on the boundary of the Martian induced magnetosphere - Jing Wang (地球与行星物理论评)
The boundary of the Mars-solar wind interaction has been investigated throughout the history of Mars space exploration. There is always a boundary between the solar wind and Mars, namely the boundary of the Martian induced magnetosphere. In the past few decades, due to the limitations of the types and accuracy of instruments on board Mars probes, the definition of the boundary of the Martian induced magnetosphere has been based on single or partial instrument data, resulting in different boundary names, such as the ion composition boundary, the induced magnetosphere boundary, and the magnetic pile-up boundary. This article briefly reviews the development of the observational studies on the boundary of the Martian induced magnetosphere along the exploration history of a series of Mars probes such as Phobos-2, MGS, MEX, and MAVEN, and summarizes the physical characteristics and definition criteria of boundaries with different names, as well as their positional relationships. Based on the comprehensive detection data of plasma and magnetic field from MAVEN, it is confirmed that the boundary of the Martian induced magnetosphere is a magnetohydrodynamic discontinuity, and its physical properties are similar to those of the Earth's magnetopause. The pile-up process of the magnetic fields occurs upstream of the discontinuity, and its properties resemble those of the plasma depletion layer upstream of the Earth's magnetopause. The relevant work clarified the structure and physical properties of the Mars-solar wind interaction boundary. The earliest knowledge of the Mars-solar wind interaction boundary came from the reporting on the plasma boundary by Phobos-2. The solar wind flow was blocked several hundred kilometers above the Martian ionosphere, forming a boundary known as the protonopause. Near the protonopause, another boundary termed the ion composition boundary (ICB), was observed that separates upstream solar wind protons from downstream planetary oxygen ions. Meanwhile, a boundary, referred to as the planetpause, characterized by the disappearance of strong electric field fluctuations was also observed. These three boundaries were believed to overlap. Lacking sufficient research on the Martian magnetic field at that time, it was not yet possible to determine whether the boundary was formed due to the solar wind blocked by the planet's intrinsic magnetic field. With more accurate plasma data on the MEX and MAVEN spacecraft, the definition of ICB has been clearer, that is, the boundary separates the plasma dominated by upstream solar wind protons and downstream Martian heavy ions (such as O+ and \begin{document}${O}_2^+ $\end{document}), and the upstream solar wind proton flow ceases at the boundary. Phobos-2 spacecraft, equipped with electromagnetic field instruments, detected the attenuation of electromagnetic field fluctuations and enhancement of the magnetic field strength in the Mars-solar wind interaction region, which are the signals of the boundary called the magnetic pile-up boundary (MPB). The MGS probe drew a comprehensive Martian global magnetic field map for the first time and also provided sufficient data for the extensive investigation of MPB. With these data, an empirical model of MPB was given. The MGS probe confirmed no global intrinsic magnetic field on Mars. Thus, the interplanetary magnetic field obstructed by the Martian ionosphere was piled up at MPB, resulting in an increase of magnetic field strength and a decrease in magnetic field fluctuations. Based on these features, the criterion of MPB was quantified using the MAVEN data. Without comprehensive data on magnetic fields and plasma around Mars previously, the Martian pressure balance boundary was in the concept and the investigations on it were also limited to the simulations. The solar wind slows down and heats up as crossing the Martian bow shock, forming the Martian magnetosheath. The dynamic pressure, thermal pressure, and magnetic pressure in the upstream magnetosheath were balanced with the thermal pressure and magnetic pressure in the downstream induced magnetosphere, forming the pressure balance boundary. Based on the comprehensive data of magnetic field and plasma on MAVEN spacecraft, statistical studies were conducted on the pressure balance boundary and provided its statistical average location. The locations of the boundaries defined above will be affected by many factors such as solar wind dynamic pressure, solar EUV, and the crustal magnetic field on Mars. However, their positional relationship is still under debate, and their physical relationship has not been explained. The latest research using the comprehensive data of plasma and magnetic field on MAVEN spacecraft shows that there is a sudden change in the magnetic field component (the orientation or magnitude) parallel to the boundary plane on the ICB, characterized by the separation of different plasma compositions and the ceasing of solar wind flow. Thus, a MHD discontinuity (including the tangential and rotational discontinuity), namely the boundary, forms with properties similar to those of the Earth's magnetopause. There are piled-up magnetic fields upstream of the boundary. In the pile-up region, the plasma is dominated by solar wind protons, and the proton energy spectrum is similar to that in the Martian magnetosheath. The proton flow slows down with the accumulation of the magnetic field and ceases until the magnetopause. Therefore, the Martian magnetic pile-up region is part of the Martian magnetosheath, with properties similar to the plasma depletion layer upstream of the Earth's magnetopause. This work clarifies the boundary structures and physical characteristics in the Mars-solar wind interaction region.